Challenges of Climate Change: Resilience Efforts in Rural Communities of Kaliwlingi Village based on Pengembangan Kawasan Pesisir Tangguh (PKPT) Program - Mustovia Azahro; Angga Dwisapta Ardi (Department of Urban and Regional Planning, Diponegoro University, 2017)
Kaliwlingi Village in Brebes City has experienced climate change impacts such as tidal flood and land abrasion. The climate change causes the dynamics of the coast and sea levels dramatically and fosters the coastal communities to have adaptation strategies. This paper aims to identify how the community of Kaliwlingi Village adapts to the climate change that affects to a social economic condition of the inhabitants. The study used qualitative method by interpreting data taken from PengembanganKawasanPesisirTangguh (PKPT) program, interviews, and observations.The study highlights that PKPT program has a significant impact, especially regarding disaster mitigation. PKPT program is successful in collecting the common rules of the community to become social capital accommodated in the local institution. Furthermore, the PKPT Program is also fostering the local economy.